The war of the sexes : how conflict and cooperation have shaped men and women from prehistory to the present - Seabright, Paul (Princeton University Press, 2012)
As countless love songs, movies, and self-help books attest, men and women have long sought different things. The result? Seemingly inevitable conflict. Yet we belong to the most cooperative species on the planet. Isn't there a way we can use this capacity to achieve greater harmony and equality between the sexes? In The War of the Sexes, Paul Seabright argues that there is--but first we must understand how the tension between conflict and cooperation developed in our remote evolutionary past, how it shaped the modern world, and how it still holds us back, both at home and at work.>